One glasses too many: A case report of Benson′s syndrome - Shivani Grover (Indian Journal of Ophthalmology, 2015)
We report a case of Benson′s Syndrome, a form of occipital Alzheimer′s disease, with posterior cortical atrophy on magnetic resonance imaging, in a 62-year-old male, who presented with visual problems, ascribed to the eyes, and had even undergone cataract/intraocular lens surgery in the right eye; and change of glasses 21 times over the past 2 years, with no apparent benefit. This case is of interest both on account of its rarity, and to highlight its features since the diagnosis may be missed in an ophthalmological setting where such patient may go for first consult.